Development of a gc–ce collaborative module grounded in the paulus makassar foundation’s core values for character education enhancement - Tandiarrang, Yulianty; Pandang, Abdullah; Buchori, Sahril (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2025)
Fragmentation between Guidance and Counseling (GC) services and Character Education (CE) often dilutes school-based efforts to cultivate students’ socio-emotional and moral development. This study developed and appraised a GC–CE collaborative module grounded in the Paulus Makassar Foundation’s core values (excellence, creativity, compassion, mission orientation) to offer an operational remedy to that fragmentation. A Research and Development design (modified Borg & Gall) was implemented through needs analysis, prototype design, expert validation, and small-scale practicality testing with GC/CE teachers and media/content experts. Results indicate a systematically articulated module—objectives, indicators, learning materials, student tasks, structured reflection, and performance rubrics—that is conceptually relevant, context-sensitive, and classroom-ready. The study advances teacher-collaboration theory by proposing a micro-collaboration framework at the session level, coupling complementary GC–CE roles with performance-based assessment and reflective supervision. This bridges value knowledge and observable behavior, extending contemporary co- teaching and school-based intervention models. The module provides a scalable guideline for schools to formalize GC–CE co-delivery, align it with PLC routines, and integrate digital/interactive formats. It can inform district-level regulations on collaborative character education and guide resource allocation (training, supervision, and monitoring). Beyond local feasibility, the model contributes a replicable, culturally responsive mechanism to strengthen holistic character education through structured teacher collaboration.